Does Mantoux Test Result Predicts BCG Immunotherapy Efficiency and Severe Toxicity in Non-Muscle Invasive Bladder Cancer - Krajewski, Wojciech; Zdrojowy, Romuald; Grzególka, Jedrzej; Krajewski, Piotr; Wróbel, Michal; Luczak, Mateusz; Kolodziej, Anna (Urology Journal, 2019)
Purpose: To evaluate on a large group of patients whether Mantoux tuberculin skin test (TST) result is associated with BCG immunotherapy effectiveness and whether it can predict occurrence of moderate to severe toxicity. Materials and Methods: We analysed group of 823 patients with intermediate and high risk NMIBCs who were treated with BCG. The study included 412 patients with the history TST and 411 without TST. A standard dose of Statens Serum Institute tuberculin RT23 was used. The reaction was read 48-72 hours later by evaluating the diameter of palpable induration. The size of the induration was considered positive when the measurement was greater than or equal to 6 mm and excessively positive when bigger than 26 mm. Whole BCG immunotherapy schedule consisted of 27 instillations. Results: The patients were followed for median 61 months. The 5-year recurrence and progression free survival (RFS, PFS) did not differ between the groups in both total study population and in tumour subgroup analysis. TST result in both total study population and in subgroups was not statistically associated with RFS, PFS and cancer specific survival. The moderate-to-severe toxicity was observed in 181(44%) TST patients, and in 196(47%) patients without TST. Incidence of toxicity was not statistically different and also not statistically associated with TST result in any of the tumour subgroups of TST group. Conclusion: This study shows, that TST does not have value in prediction of bladder cancer recurrence, progression nor cancer specific survival. Also it doesn’t have a value in predicting therapy toxicity.